A Potential Mechanism of Kidney-Tonifying Herbs Treating Unexplained Recurrent Spontaneous Abortion: Clinical Evidence From the Homogeneity of Embryo Implantation and Tumor Invasion - Zhou, Hang; Yang, Yi; Deng, Linwen; Yao, Yongqing; Liao, Xin (Frontiers in Pharmacology, 2022)
BACKGROND Kidney Tonifying Herbs (KTH) is widely used to treat unexplained recurrent spontaneous abortion (URSA) based on the theory of traditional Chinese medicine. However, there is still a lack of systematic evaluation and mechanistic explanation of the treatment. OBJECTIVE The purpose of this study is to assess the clinical efficacy and investigate potential mechanisms of KTH based on traditional Chinese medicine (TCM) in the treatment of URSA. METHOD A systematic literature search was conducted in PubMed, EMBASE, China biomedical literature database, China National Knowledge Infrastructure database and Wanfang database to find articles that report Chinese herbal formula-based KTH in treating URSA, are published between January 2010 and June 2021, and use randomized controlled trials (RCTs). We also used network Pharmacology Method to detect the potential pathway of KTH in the treatment of URSA. RESULTS The meta-analysis included nine randomized controlled trials involving 1054 subjects. Compared with the control group, the clinical efficacy of TCM-based KTH in the treatment of URSA patients was significantly improved. Additionally, a component target pathway network was identified, including 32 potential blood activating components and 113 main targets. The key potential therapeutic pathway for URSA was tumor-related signaling pathway. CONCLUSION KTH has great potential in the treatment of URSA. To further improve the efficacy of KTH-based treatment, large-scale, high-quality clinical trials and validation experiments should be conducted. We should also keep track of the research of tumor-related mechanisms, in order to bring new ideas and breakthroughs for the research of URSA.